EFFECTS OF ADDING ZINC OXIDE(ZNO) ON THICK (PMMA) FILMS (World Bulletin of Public Health, 2023)
In this research, a group of materials were used, including poly methyl methacrylate (PMMA) as a base material with chloroform as a pure solvent (99.8%) with zinc oxide (ZnO) as an additive to the base material by (50%) The effects of addition on the X-ray diffraction spectrum were shown. (XRD) the base material to which zinc oxide (ZnO) was added through the distinctive peaks that gave the character of crystallization, while the effect on the thick film appeared in the scanning electron microscopy (SEM) in the form of some nodal structures of (nm) dimensions that were visible on the structure of the base material.
Keywords: ZnO; PMMA; Effects of adding